A organização do trabalho: um estudo dos trabalhadores em reabilitação profissional do INSS - Souza, Andréa Domingues da Silva [UNIFESP] (2016)
This study aimed to encourage discussion in group of injured and sickned workers who are in the Vocational Rehabilitation of Social Security, in relation to aspects of the organization of work, the male and the health of workers, thus enabling appropriate coping their limited condition at work and recognize their rights and transformative potential, given that there is currently space INSS. The research has hypothesized that man to understand that the healthdisease suffer interference from the capital x labor relations, and in this context the role culturally assigned to men, it will reflect on the rights acquired order to exercise the role of citizen and may find potential for better work life and out of it and, if possible, effectively exercise professional rehabilitation. Therefore the method was based on qualitative research, intervention research, with workshops feature. There were two groups, totalized the participation of 23 male workers, and a group of 11 participants and the other with 12 participants, aged 35-46, who spent on care in Vocational Rehabilitation Services, INSS - Agency Social welfare Guarulhos, from August / 2013 to January / 2014. The workshops took place in Occupational Health Reference Center - Guarulhos, lasting two hours and a total of six meetings per group. In the analysis it was decided by the collective subject discourse method. The data collected show results pointing out that workers recognize that work and work is vital to man, it establishes with him a relation of identity, dignity, and when you do not see more in this process, there is a feeling of worthlessness shall lose if the meaning of life. The work is recognized by man as a condition of its existence, however, due to changes in the world of work by the interests of capital, the worker does not recognize the work beyond the exchange relation, and thus alienates the world work, which increasingly intensified forms of exploitation of the working class. Present the reality of the current labor organization characterized as precarious, oppressive, and be worker exploitation that sometimes undergoes certain attitudes both by fear of unemployment as by too much competition in the labor market, which places worker in a competitive environment both in the workplace and in the search for replacement. Recognize that working conditions as well as the current requirements of the labor market can influence illness or accident at work, and so consequently the withdrawal occurs. Workers recognize that work brings pleasure, satisfaction, personal growth that will lead to life. But they have "brands" negative which will also lead to a lifetime because they generate suffering, guilt, beyond the emotional pain related to social judgment due to the remoteness, and the feeling of abandonment for enterprises when the removal of the work occurs. The study also points out the uncertainty regarding the continuation or not of benefit as well, as the working man feels humiliated by not meet the family's needs because of the low value of the benefit. They evaluated the study process who participated as positive, and that the group enabled a living space, exchange of experience and listening. This study also allowed the opening of a debate in the Vocational Rehabilitation team for the construction of group actions, and the importance of intersectoral action and the process of education and health education with the workers away due to accident or illness related to work.